Proteomic analysis of serum in patients with non-alcoholic steatohepatitis using matrix-assisted laser desorption ionization time-of-flight mass spectrometry - ATUĞ, ÖZLEN; YILMAZ, YUSUF (TAYLOR & FRANCIS LTD, 2009)
Objective. We sought to investigate whether serum proteomic pattern analysis obtained using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI TOF-MS) may help to diagnose non-alcoholic steatohepatitis (NASH) in the setting of non-alcoholic fatty liver disease (NAFLD). Material and methods. We enrolled 80 patients with biopsyproven NAFLD and 19 healthy comparison subjects. Patients with NAFLD were classified according to their liver histology as having definite NASH (n = 48), borderline NASH (n = 22) or simple steatosis (n = 10). Liver ultrasound scanning was performed to assess the degree of steatosis. Mass spectra of serum samples were obtained using a Ultraflex II mass spectrometer. Results. The highest accuracy for NASH diagnostics was reached using 15 peaks. Corresponding sensitivity and specificity values were 73.95% +/- 3.38% and 88.71% +/- 1.39%, respectively. However, mass spectra did not allow us to distinguish NASH from simple steatosis. Conclusions. We conclude that proteomic analyses of serum samples from NAFLD patients by MALDI TOF-MS do not seem to have a major clinical value for diagnosing NASH. However, the identification of 15 peaks in our study may help to further elucidate the pathophysiology of NASH and merits further investigation.
Keywords: Matrix-assisted laser desorption ionization time-of-flight mass spectrometry; non-alcoholic fatty liver disease; non-alcoholic steatohepatitis; proteomics; serum; FATTY LIVER-DISEASE; DIAGNOSIS; FIBROSIS